2015
DOI: 10.1016/j.anbehav.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Going with, then against the flow: evidence against the optomotor hypothesis of fish rheotaxis

Abstract: Movement through an environment provides sighted organisms with dynamic visual cues known as optic flow. In flying insects, optic flow is important for collision avoidance, flight speed control and landing manoeuvres. The function of optic flow is much less understood in other taxa, particularly in fish. Despite a lack of quantitative studies, optomotor responses (OMRs) to optic flow are presumed to be nearly ubiquitously important for rheotaxis (orientation to currents), a widespread behaviour that confers a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 46 publications
3
28
0
Order By: Relevance
“…Moreover, the paired t-test further depicted that there was a statistically significant difference in the transportation time with the presence and absence of visual cues (paired sample t-test, p-value < 0.01), indicating the dominance of visual cues over hydromechanical cues even within the microfluidic environment. This agrees well with the literature, where authors have highlighted that within open channels, visual cues dominate larval behavior [14,16,17]. However, it was further observed that with the sole presence of hydromechanical cues, zebrafish larvae could be transported efficiently within the microfluidic environment at relatively higher flow rates of 0.2 and 0.3 mL/min.…”
Section: Behavioral Responses Corresponding To Optical and Hydrodynamsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the paired t-test further depicted that there was a statistically significant difference in the transportation time with the presence and absence of visual cues (paired sample t-test, p-value < 0.01), indicating the dominance of visual cues over hydromechanical cues even within the microfluidic environment. This agrees well with the literature, where authors have highlighted that within open channels, visual cues dominate larval behavior [14,16,17]. However, it was further observed that with the sole presence of hydromechanical cues, zebrafish larvae could be transported efficiently within the microfluidic environment at relatively higher flow rates of 0.2 and 0.3 mL/min.…”
Section: Behavioral Responses Corresponding To Optical and Hydrodynamsupporting
confidence: 92%
“…Although it is far from fully understanding the complicated behavioral dynamics of zebrafish larvae, the research fraternity widely believes that the lateral line of the zebrafish body mediates the orientation of the body against incoming flow and that the optomotor response (OMR) mediates counterflow [14][15][16][17]. In their natural surroundings, velocity gradients are created through nearby obstructions when the zebrafish larvae encounter a sheared flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support the view that zebrafish visual system and perception (in particular, motion perception) rely on similar principles commonly found in humans. On the other hand, although there are studies comparing larval responses to visual stimulation (e.g., motion) with that of adult zebrafish [49], there is almost no systematic investigation on perceptual changes during aging. Future studies examining age-related changes in zebrafish perception and perceptual acuity will be informative in this respect and are currently being performed in our laboratory.…”
Section: Age-related Changes In Zebrafish Perceptual and Cognitive Pementioning
confidence: 99%
“…Optic flow. Like many other animals, zebrafish larvae generate optokinetic responses of the eyes (OKR) and optomotor responses of the body (OMR) when exposed to visual stimuli simulating egomotion of the fish [2,8]. Both eye-and body movements generate space-variant patterns of local motion vectors on the retina which then have to be analyzed by subsequent processing stages.…”
Section: Introductionmentioning
confidence: 99%